Strategi Pengembangan dan Pemasaran Cheezy Chix Roll sebagai Produk Kuliner Kreatif - Mohammad Afrizal miradji; Gracia Amry Virginia; Ajeng Margareta; Novi Lailatul Fitri; Citra Devy Arista; Fitrianti Rahma Novitasari; Wanudya Ajeng Ferara (Journal of Economics, Management, and Accounting, 2025)
This study aims to analyze the development and marketing strategies of Cheezy Chix Roll as a creative culinary innovation amid increasingly competitive food industry competition. The study uses an exploratory descriptive method with a qualitative approach, focusing on culinary trend observation, literature study, and SWOT analysis to identify the product's strengths, weaknesses, opportunities, and threats. The results show that flavor innovation, raw material quality, and attractive packaging are key factors in increasing the competitiveness of Cheezy Chix Roll. On the other hand, digital marketing strategies through social media such as Instagram and TikTok have proven to be effective in expanding market reach and building brand awareness, especially among the younger generation. The SWOT analysis indicates that the product's main strengths lie in its unique taste and potential to go viral on social media, while its main threats come from market competition and rapidly changing culinary trends. Therefore, the long-term success of Cheezy Chix Roll depends on consistency in product innovation, the implementation of environmentally friendly packaging, and the optimization of sustainable digital promotion strategies.